The use of a benign fast-growing cyanobacterial species to control microcystin synthesis from Microcystis aeruginosa - Lee, Hakyung; Xu, Vincent; Diao, Jinjin; Zhao, Runyu; Chen, Moshan; Moon, Tae Seok; Liu, Haijun; Parker, Kimberly M.; Jun, Young-Shin; Tang, Yinjie J. (Frontiers in Microbiology, 2024)
IntroductionMicrocystis aeruginosa (M. aeruginosa), one of the most abundant blue-green algae in aquatic environments, produces microcystin by causing harmful algal blooms (HABs). This study investigated the combined effects of nutrients and competition among cyanobacterial subpopulations on the synthesis of microcystin-LR.MethodsUnder varying nitrogen and phosphorus concentrations, cyanobacterial coculture, and the presence of algicidal DCMU, the growth was monitored by optical density analysis or microscopic counting, and the microcystin production was analyzed using high-performance liquid chromatography-UV. Furthermore, growth and toxin production were predicted using a kinetic model.Results and discussionFirst, coculture with the fast-growing cyanobacterium Synechococcus elongatus UTEX 2973 (S. elongatus) reduced M. aeruginosa biomass and microcystin production at 30°C. Under high nitrogen and low phosphorus conditions, S. elongatus was most effective, limiting M. aeruginosa growth and toxin synthesis by up to 94.7% and 92.4%, respectively. Second, this biological strategy became less effective at 23°C, where S. elongatus grew more slowly. Third, the photosynthesis inhibitor DCMU (3-(3,4-dichlorophenyl)-1,1-dimethylurea) inhibited M. aeruginosa growth (at 0.1 mg/L) and microcystin production (at 0.02 mg/L). DCMU was also effective in controlling microcystin production in S. elongatus–M. aeruginosa cocultures. Based on the experimental results, a multi-substrate, multi-species kinetic model was built to describe coculture growth and population interactions.ConclusionMicrocystin from representative toxin-producing M. aeruginosa can be controlled by coculturing fast-growing benign cyanobacteria, which can be made even more efficient if appropriate algicide is applied. This study improved the understanding of the biological control of microcystin production under complex environmental conditions.